The Valuation of Financial Derivatives Subject to Counterparty Risk and Credit Value Adjustment - Tim Xiao (ZBW – Leibniz Information Centre for Economics, 2019)
This article presents a generic model for pricing financial derivatives subject to counterparty credit risk. Both unilateral and bilateral types of credit risks are considered. Our study shows that credit risk should be modeled as American style options in most cases, which require a backward induction valuation. To correct a common mistake in the literature, we emphasize that the market value of a defaultable derivative is actually a risky value rather than a risk-free value. Credit value adjustment (CVA) is also elaborated. A practical framework is developed for pricing defaultable derivatives and calculating their CVAs at a portfolio level.
Keywords: E44; G21; G12; G24; G32; G33; G18; G28; 330; credit value adjustment (CVA); credit risk modeling; financial derivative valuation; collateralization; margin and netting